2017
DOI: 10.1139/gen-2016-0146
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal distribution patterns of the (AC)10 microsatellite and other repetitive sequences, and their use in chromosome rearrangement analysis of species of the genus Avena

Abstract: Fluorescence in situ hybridization (FISH) was used to determine the physical location of the (AC) microsatellite in metaphase chromosomes of six diploid species (AA or CC genomes), two tetraploid species (AACC genome), and five cultivars of two hexaploid species (AACCDD genome) of the genus Avena, a genus in which genomic relationships remain obscure. A preferential distribution of the (AC) microsatellite in the pericentromeric and interstitial regions was seen in both the A- and D-genome chromosomes, while in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 57 publications
5
50
1
Order By: Relevance
“…Clustered and Avena longiglumis (Al genome) karyotypes, we indicated one pair of chromosomes with the similar pattern of multiple rDNAs localization (large terminal 35S rDNA and distal 5S rDNA sites in the short arm and also interstitial 5S rDNA loci in the long arm). The similar chromosome pair was earlier described in diploid and polyploid Avena species with different types of the A genome [30][31][32][33][34], and it could be inherited from a common progenitor at a remote period. In karyotypes of A. latifolia, H.…”
Section: Dapi-banding Analysissupporting
confidence: 58%
See 1 more Smart Citation
“…Clustered and Avena longiglumis (Al genome) karyotypes, we indicated one pair of chromosomes with the similar pattern of multiple rDNAs localization (large terminal 35S rDNA and distal 5S rDNA sites in the short arm and also interstitial 5S rDNA loci in the long arm). The similar chromosome pair was earlier described in diploid and polyploid Avena species with different types of the A genome [30][31][32][33][34], and it could be inherited from a common progenitor at a remote period. In karyotypes of A. latifolia, H.…”
Section: Dapi-banding Analysissupporting
confidence: 58%
“…Currently, detailed cytogenetic information is available for less than half of the altogether 60-70 genera of the Aveneae/Poeae [15,29], and among them, the genus Avena is the most extensively studied with the use of FISH with different sat DNAs and staining of constitutive heterochromatin regions on chromosomes [30][31][32][33][34]. Molecular phylogenetic and cytogenetic studies indicated that diploid Avena species carried different types of the A genome (As; Al; Ac; Ad and Ap) or C genome (Cv and Cp); tetraploid Avena species (2n = 4x = 28) comprised AB or AC genomes; and hexaploid species (2n = 6x = 42) had ACD genomes [16][17][18][19][20][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The trinucleotide repeat probe (ACT) 6 also showed large loci in C genome. Fominaya et al (2017) reported a preferential distribution of (AC) 10 in the pericentromeric and interstitial regions of A-and D-genome chromosomes and in the pericentromeric heterochromatic regions of C-genome chromosome. The location of the trinucleotide repeat probe (ACT) 6 loci at either the middle or termini (or even at both the middle and terminus of an individual chromosome) show the diverse distribution of hybridization patterns in species of Avena.…”
Section: Diverse Patterns Of the A Ab C Ac And Acd Genomesmentioning
confidence: 99%
“…Oligonucleotides, except for (AC) 10 , have rarely been used as FISH probes in species of Avena (Fominaya et al 2017), but they have been widely used for species of other genera, including Triticum aestivum (Cuadrado et al 2008;Tang et al 2014), Secale cereal (Fu et al 2015), Leymus mollis , Aegilops triuncialis (Mirzaghaderi et al 2014), and Thinopyrum intermedium (Li et al 2016). Since none of the genomes in Avena have been published, knowledge of the locations of repeat elements could be very important in the assembly of genome sequences and their assignment to physical chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, in karyotypes of vascular plants, DAPI staining, performed after FISH or GISH procedures, reveals AT-rich heterochromatin which consists largely of highly repetitive ('satellite') DNA) as strongly stained bands [67]. Currently, microsatellite DNA sequences are widely used as FISH probes for cytogenetic studies as they are major components of many plant genomes [33,34,71,72]. Particularly, it has been recently determined that FISH with the oligo-GTT probe produces six constant signals located in the pericentromeric regions of three chromosome pairs of diploid A genome Avena species with minor interspecies differences in signal intensity [34].…”
Section: Dapi-banding Analysismentioning
confidence: 99%